Analisis Penerapan E-Bupot 21/26 dalam Melaporkan Pajak Penghasilan (PPH) Pasal 21 Atas Karyawan Tetap pada PT XYZ di Surabaya - Septya Asmoro Wati; Muslimin Muslimin (AKUNTANSI 45, 2024)
This study aims to analyze the application of e-Bupot 21/26 in reporting Income Tax (PPh) Article 21 on permanent employees at PT XYZ in Surabaya. This study uses a descriptive method with a qualitative approach. Data was obtained through interviews and documentation from the company’s finance and tax departments. The results of the study show that PT XYZ has implemented the e-bupot application to report Income Tax Article 21 in accordance with applicable tax regulations, but there are several obstacles faced in the reporting process. This research is expected to contribute to improving the company’s tax system and increasing compliance with tax regulations.